Computer Technology-Based MBKM to Develop Mathematics Education Students Metacognition and Metaskill Perspective - Sugilar, Hamdan; Mangkuwibawa, Hilman; Yudhiantara, Rully Agung (Jurnal Educative: Journal of Educational Studies, 2023)
This research endeavors to assess the allocation of mathematics education courses concerning mathematics computer technology, metacognition, and meta-skills in mathematics learning. It also aims to gauge the outcomes of mathematical metacognition abilities through the utilization of mathematical computer applications. Employing a mixed-method approach, the study simultaneously gathered and analyzed qualitative and quantitative data. Quantitative data were derived from the outcomes of metacognition abilities, while qualitative information was obtained from curriculum documents and metacognition abilities. The metacognition thinking ability test comprised 10 short descriptions related to differential and integral calculus material. The participants were 45 seventh-semester students majoring in mathematics education during the 2021/2022 academic year at UIN Sunan Gunung Djati Bandung, all of whom undertook mathematics computer application courses. The findings indicate that the mathematics education study program has implemented a curriculum fostering the attainment of qualifications for graduates adept at applying mathematical computer technology, evidenced by the distribution of computer technology-based courses. Metacognition and meta-skills are deemed essential in preparing prospective teachers to engage in higher-level thinking and effectively apply new knowledge, particularly through the application of mathematical computer programs. Notably, students demonstrated good metacognition abilities based on the assessment results.Tujuan penelitian ini adalah untuk mengetahui sebaran mata kuliah pendidikan matematika berbasis teknologi komputer matematika, metakognitif dan meta skill pada pembelajaran matematika, dan hasil kemampuan metakognitif matematik dengan menggunakan aplikasi komputer matematika. Metode penelitian ini adalah mix method dengan pendekatan penelitian integrative, data kualitatif dan kuantitatif dikumpulkan secara bersamaan dan dianalisis. Metode kuantitatif berupa hasil kemampuan metakognitif, data kualitatif berupa dokumen kurikulum dan kemampuan metakognitif. Analisis data berupa hasil tes kemampuan berpikir metakognitif terdiri dari 10 uraian singkat terdiri dari materi kalkulus diferensial dan integral. Subjek penelitian adalah 45 mahasiswa semester VII tahun akademik 2021/2022 pendidikan matematika UIN Sunan Gunung Djati Bandung yang menerima mata kuliah aplikasi komputer matematika. Hasil penelitian diperoleh bahwa program studi pendidikan matematika telah mengimplementasikan kurikulum yang mendorong capaian kualifikasi lulusan terampil mengaplikasikan dan memanfaatkan teknologi komputer matematika berupa sebaran mata kuliah berbasis teknologi komputer. Metakognitif dan meta skill dibutuhkan untuk menyiapkan mahasiswa calon guru untuk mampu berpikir tingkat tinggi dan terampil menggunakan pengetahuan baru berupa penerapan aplikasi komputer matematika. Hasil kemampuan metakognitif mahasiswa dalam kategori baik.